Utilization of Environmentally Minded Open Space on New Normal Era - Reflis, Reflis; Cahyadinata, Indra; Utama, Satria Putra (Universitas Muhammadiyah Palembang, 2021)
Indonesia has been battling Covid-19 by modifying the regional quarantine (lockdown) policy into large-scale social restrictions (LSSR) that are local according to the severity of the region. The government is trying to regulate the New Normal policy to avoid a prolonged economic impact that can cause a crisis. The objectives of this Community Service (CS) activity are: 1) To encourage people to stay productive in the new standard era by doing activities around the house. 2) Inviting the community to organize environmental space and use of the yard. Most people in the Villa Pabittei housing estate, Bengkulu City, Bengkulu Province are civil servants, temporary or non-permanent employees, so they carry out their activities at home because the government has closed offices and schools. To anticipate the boredom of the people who laid off, the methods of this CS activity are 1) Counseling using learning by doing techniques and providing motivation for the community to use vacant land with FMP (family medicinal plants), 2) Simulation of structuring space into an environmental park